2009
DOI: 10.1371/journal.pntd.0000350
|View full text |Cite
|
Sign up to set email alerts
|

Mefloquine—An Aminoalcohol with Promising Antischistosomal Properties in Mice

Abstract: BackgroundThe treatment and control of schistosomiasis, an often neglected tropical disease that exacerbates poverty, depends on a single drug, praziquantel. The large-scale use of praziquantel might select for drug-resistant parasites, hence there is a need to develop new antischistosomal compounds. Here, we report that the antimalarial drug mefloquine possesses promising antischistosomal properties in mice.Methodology/Principal FindingsA single dose of mefloquine (200 or 400 mg/kg) administered orally to mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
156
1
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(181 citation statements)
references
References 44 publications
14
156
1
6
Order By: Relevance
“…In areas with heavy transmission of schistosomiasis, it has been suggested that people might have been infected in the previous 3-5 weeks. Hence, such patients would harbor immature schistosomes that are less susceptible to PZQ [7,[39][40][41] . These immature stages have the high chance to survive a single treatment and mature to deposit eggs in the subsequent weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In areas with heavy transmission of schistosomiasis, it has been suggested that people might have been infected in the previous 3-5 weeks. Hence, such patients would harbor immature schistosomes that are less susceptible to PZQ [7,[39][40][41] . These immature stages have the high chance to survive a single treatment and mature to deposit eggs in the subsequent weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, schistosomicidal compounds such as artemether and mefloquine have been studied for their efficacy against schistosomes [6][7][8][9] . However, praziquantel (PZQ) remains the drug of choice in the treatment of schistosomiasis since the 1970s [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…As described in a previous study, P. vinckei-infected mice treated with 50 mg/kg of pepstatin A showed no toxic signs, and the in vivo effect was improved by combinations of AP and peptidyl cysteine inhibitors. 20 Mefloquine was used for treatment of mice infected with Schistosoma mansoni and S. japonicum 43 and of hamsters infected with Opisthorchis viverrini 44 at concentrations of 100-400 mg/kg for 2-4 weeks. There were no signs of toxicity observed in the murine model.…”
Section: Discussionmentioning
confidence: 99%
“…activity (Rollas & Kuçukguzel, 2007). The most recent researches on new compounds or drugs with schistosomicidal activity have been carried out with: a) inhibitors of cysteine protease, such as K11777, considered a powerful schistosomicide that reduces the pathogenesis of experimental schistosomiasis (Abdulla et al, 2007), b) RNAi, in the attempt to develop drugs or compounds that act as enzyme silencers, e.g., the compound 4-phenyl-1,2,5-oxadiazole-3-carbonitrile-2-oxide, or furoxan, which acts on thioredoxin-glutathione reductase from S. mansoni (Kuntz et al, 2007, Sayed et al, 2008, c) trioxolanes or secondary ozonides (1, 2, 4-trioxolanes), which comprehend a class of synthetic endoperoxides that are cheap, easily synthesised, and similar to artemisinins, having activity on experimental infections with S. mansoni and S. japonicum (Caffrey, 2007, Xiao et al, 2007, d) mefloquine (antimalarial), which showed schistosomicidal activity against young and adult S. mansoni worms (Van Nassauw et al, 2008, Keiser et al, 2009), e) arachidonic acid, which showed schistosomicidal properties against S. mansoni and S. haematobium ( E l R i d i e t a l . , 2010), and f) miltefosine (antileishmania), which reduced the parasite burden of mice infected with S. mansoni (Eissa et al, 2011).…”
Section: Chemotherapy Against Schistosomiasismentioning
confidence: 99%